Adopting ecological restoration goals as a critical goal in mining tailings mitigation: a methodological proposal - Márquez-Huitzil, Roberto; Martínez-Garza, Cristina; Osorio Beristain, Marcela (Instituto de Ecología, A.C., 2022)
Background and Aims: In Mexico there are accumulations of toxic and unstable materials discarded by mining, called tailings, which represent a potential and effective risk for ecosystems and society. Ecological restoration in combination with other mitigation strategies offer an alternative to mitigate these environmental impacts and reverse the ecosystem degradation caused by tailings. This work raises some considerations and proposes a methodology to apply the ecological restoration to tailings.Methods: The effects and risks caused by the deposit of tailings in the open pit were described based on the characteristics of the materials and the ecosystem in which they are deposited, applying and adapting criteria such as those used in the Evaluation of the Ecological Impact. Based on this, some guidelines and considerations were proposed to mitigate tailings. The limitations of some mitigation techniques with organisms or organic matter were also analyzed, due to their potential collateral impacts.Key results: The methodological proposal considers actions to mitigate a mining tailing that integrate the ecosystem and its functioning, directed towards an ecosystem restoration. On the one hand, these guidelines consider aspects related to the toxicity and stability of tailings and, on the other hand, the characteristics and ecosystem processes affected by their deposit. This proposal considers ten steps that incorporate different aspects that must be addressed to achieve restoration in tailings deposits.Conclusions: Through an ecosystem approach, as in ecological restoration, the environmental problems of contamination and instability of the tailings are solved. Also avoiding the collateral impacts of the mitigation strategies themselves, such as the creation of ecological traps or making contaminants bioavailable, introducing them into the food chain without compensating for the ecosystem impacts caused by their deposit.